Spent Bleaching Earth Supported CeFeO3 Perovskite for Visible Light Photocatalytic Oxidation of Methylene Blue - Edy Saputra; Panca Setia Utama; Irdoni HS; Marihot Danield Vyendri Simatupang; Barata Aditya Prawiranegara; Hussein Rasool Abid; Oki Muraza (Journal of Applied Materials and Technology, 2020)
Dyes substances from the textile industry wastewater are internationally classified as poisonous substances, and they cause a severe threat to humans being and other living things, even at low concentrations. Therefore, this waste has to be treated before discharge to the environment. One of the most effective processes for degrading dyes is photocatalytic oxidation. Two different pretreatments of Spent bleaching earth (SBE) from palm oil refinery plant were applied to produce catalyst supports. The SBEe support was prepared by extraction using n-hexane, SBEc by calcination at 500 oC, and then used as a support for CeFeO3/SBEe and CeFeO3/SBEc perovskite catalyst. Both catalysts were tested for the degradation of methylene blue (MB) using photocatalytic oxidation. The properties of catalysts were characterized using some characterization methods, such as thermogravimetric-differential thermal analysis (TG-DTA), X-ray diffraction (XRD), scanning electron microscope (SEM) equipped with Dispersive Energy X-ray Spectroscopy (EDS), specific surface area (BET) and pore size analysis. CeFeO3/SBEe catalyst was found more efficient in photocatalytic oxidation for MB compared with the CeFeO3/SBEc catalyst. CeFeO3/SBEe catalyst could degrade 99.5% of MB during 120 min, at the condition of 25 mg/L MB, 1.0 g/L catalyst, and pH 7. The effect of pH on the performance of the catalyst followed the order of pH 7 > pH 9 > pH 5. Moreover, the CeFeO3/SBEe catalyst demonstrated excellent activity in the degradation of MB, displaying that CeFeO3/SBEe is a favorable catalyst for water purification.